Prion protein modulates iron transport in the anterior segment: Implications for ocular iron homeostasis and prion transmission. (October 2018) - Ashok, Ajay; Karmakar, Shilpita; Chandel, Rajeev; Ravikumar, Ranjana; Dalal, Stuti; Kong, Qingzhong; Singh, Neena
Abstract: Iron is an essential biometal in the aqueous humor, the principal source of nutrients for the avascular cornea and the lens. Here, we explored whether the ciliary body (CB), the source of aqueous humor, transports iron, and if the prion protein (PrP C ) facilitates this process as in the outer retina. Using a combination of human, bovine, and mouse eyes as models, we report the expression of iron export proteins ferroportin and ceruloplasmin, and major iron uptake and storage proteins transferrin, transferrin receptor, and ferritin in the ciliary epithelium, indicating active exchange of iron at this site. Ferroportin and transferrin receptor are also expressed in the corneal endothelium. However, the relative expression of iron export and uptake proteins suggests export from the ciliary epithelium and import by corneal endothelium. In addition, abundant expression of PrP C, a ferrireductase that facilitates iron transport, is noted in pigmented and non-pigmented epithelium of the CB, posterior pigmented epithelium of the iris, corneal endothelium and epithelium, and lens epithelium. Notably, majority of PrP C in the ciliary epithelium is cleaved at the β-site as in retinal pigment epithelial cells, suggesting a role in iron transport. Most of the PrP C in the cornea, however, is full-length, and susceptible to aggregation by intracerebrally inoculated PrP-scrapie, an infectious conformation of PrP C responsible for human and animal prion disorders. Soluble PrP C is present in the aqueous and vitreous humor, a provocative observation with significant implications. Together, these observations suggest independent cycling of iron in the anterior segment, and a prominent role of PrP C in this process. Aggregation of PrP C in the cornea of PrP-scrapie-infected animals raises the alarming possibility of transmission of animal prions through corneal abrasions. Highlights: Non-pigmented ciliary epithelium exports iron to the aqueous humor. PrP C modulates iron transport across ciliary epithelium and corneal endothelium. Soluble PrP C is present in the aqueous and vitreous humor. Prion infection induces aggregation of PrP C in the cornea and ciliary epithelium.